Seroprevalence and Risk Factors of Toxoplasmosis in Togo - Amivi Tété-Bénissan; Mlatovi Dégbé; Holoud Maman; Abiba K. Banla; Agnon Balogou; Kodjo Aklikokou; Messanvi Gbeassor (European Scientific Journal, ESJ, 2018)
Objectives: Toxoplasmosis is caused by Toxoplasma gondii. 50 to 70% of African are contaminated and 60% to 80% in Togo. This parasitic infection involves disorders in immunocompromised persons and pregnant women. The purpose of this study is to evaluate the seroprevalence of toxoplasmosis and the risk factors of contamination in the Togolese population. Methods: Prospective studies from January 2012 to December 2015 concerned 7076 patients. A survey on the risk factors for Toxoplasma gondii contamination has done. The seroprevalence was monitored by examining serological antibodies IgG and IgM using ELISA method. Sampling of 200 excreta of domestic cats were analyzed by coproscopy examinations Results: The average age was 32.61±6.80 years old. The seroprevalence of IgM was 2.85%; and for IgG 59.7%. IgG were high in men (67.0% vs. 58.6%, p<0.0001); IgM were high in women (2.81% vs. 1.85%, p<0.01). In this study, we observed 57.49% immunized subjects. Regarding potential risk factors for contamination, the survey revealed that 80.5% of subjects consume raw garden produce, 65.4% non-potable and 8.3%  undercooked meat. In cats, 20.5% of them excreted oocysts of Toxoplasma gondii. Conclusion: The prevalence of the toxoplasmosis was high in the Togolese population because the risks factors were variable and the level of contamination were high too. The country’s health authorities, especially for the pregnant women, should install sensitization and prevention programs on the risks of the contamination of toxoplasmosis. The high proportion of the young subjects affected constitutes a socio-economical danger for the country.